Criteria for choosing a hyaluronic acid preparation for intra-articular administration in patients of different ages with osteoarthritis of the knee joint - D. I. Otvetchikova; E. N. Ryabkov (Лечащий Врач)
To date, the search for optimal approaches to the conservative treatment of patients with osteoarthritis (OA) is an urgent problem. This is due to the prevalence, multifactorial of the disease, as well as an increase in the incidence of OA among young patients. In the early stages of the disease, as well as in the treatment of young patients, doctors prefer to choose the non-surgical treatment. In OA, the most vulnerable structure of the joint is hyaline cartilage. In degenerative-dystrophic diseases, it becomes thinner, and the synovial fluid in OA tends to lose its elastic properties. To reduce the load on the articular cartilage, (prostheses) of synovial fluid – hyaluronic acid (HA) are actively used. HA is a natural component of synovial fluid, it serves as a lubricant for articular surfaces and provides a number of protective and regulatory effects. The HA injected from the outside takes on the load, compensating for the lost properties of the joint's own synovial fluid. So GC drugs are able to quickly relieve pain and return activity to the patient. During treatment, the choice of the HA drug should depend on the phenotype, age, stage of the disease, concomitant somatic pathology, daily physical activity and individual needs of the patient. The doctor selects a HA drug of different molecular weight, structure and concentration. As a consequence, the number of injections per course of treatment may also vary. It is necessary to evaluate in more detail the criteria for selecting the GC drug to improve the quality of treatment and results in the long term. The analysis of the literature data devoted to the selection of GC drugs presented on the domestic market, depending on the stage of the disease and the age of the patient.